Development and Characterization of Innovative Fiber Reinforced Prepregs and Their Composites Containing Functional Fillers - Uz, Yusuf Can; Tanoğlu, Metin (Izmir Institute of Technology, 2021)
This Ph.D. thesis aims to prepare laboratory-scale carbon fiber reinforced prepregs and improve the performance of their composites by incorporating functionalized single-wall carbon nanotubes (SWCNTs). The effect of nano-scale functional fillers on the characterization of prepregs and their composites was investigated to develop innovative materials for primary structures. To affect dispersion characteristics, SWCNTs were functionalized by oxidizing their surface with the carboxyl (-COOH) group using acid treatment. The modified resin system containing 0.05, 0.1, and 0.2 wt. % F-SWCNTs were developed with novel multi-step dispersion techniques. FTIR spectroscopy was performed to identify new bonding groups formed after the covalent functionalization. Unidirectional carbon fiber reinforced prepregs with/without F-SWCNTs were prepared using a drum-type winding technique by utilizing the solvent-dip (solution impregnation) process. The effect of F‐SWCNTs on the curing process and kinetic parameters of the carbon fiber/epoxy-based prepregs were investigated using non‐isothermal DSC. The activation energy of the curing reaction was calculated by the isoconversional methods. Also, the new numerical approach called GMN was developed to determine the activation energy of the thermosetting materials. For the fabrication of prepreg-based composite laminates, the vacuum bag-only (VBO) method was performed. The fiber volume fractions of the CFRP samples changed between 55.3% and 50.16%. The mechanical and thermomechanical properties of prepreg-based CFRP composites with/without F-SWCNTs were investigated. The optimum mechanical properties of F-SWCNTs filled CFRP composite was achieved at 0.05 wt.% of F-SWCNTs. However, mechanical properties were decreased due to the addition of higher content of F-SWCNTs, in comparison with neat CFRP.

Bu doktora tezinin amacı, laboratuvar ölçeğinde karbon fiber takviyeli prepregler hazırlamak ve işlevselleştirilmiş tek duvarlı karbon nanotüpler (SWCNT'ler) dahil ederek onların kompozitlerinin performansını iyileştirmektir. Nano ölçekli fonksiyonel dolgu maddelerinin prepreglerin ve bunların kompozitlerinin karakterizasyonu üzerindeki etkisi, birincil yapılar için yenilikçi malzemeler geliştirmek için araştırıldı. Dağılım özelliklerini etkilemek için, SWCNT'ler, bir asit muamelesi kullanılarak yüzeylerini karboksil (-COOH) grubu ile oksitleyerek işlevselleştirildi. Ağırlıkça %0.05, 0.1 ve 0.2 F-SWCNT'ler içeren modifiye reçine sistemi özgün çok adımlı dispersiyon teknikleriyle geliştirilmiştir. Kovalent işlevselleştirmeden sonra oluşan yeni bağlanma gruplarını belirlemek için FTIR spektroskopisi yapıldı. F-SWCNT'li / F-SWCNT'siz tek yönlü karbon fiber takviyeli prepregler, solvent daldırma (çözelti emdirme) işlemi ile tambur tipi sarma tekniği kullanılarak hazırlandı. F-SWCNT'lerin karbon fiber/epoksi bazlı prepreglerin kürleme süreci ve kinetik parametreleri üzerindeki etkisi, izotermal olmayan DSC kullanılarak araştırıldı. Kürleme reaksiyonunun aktivasyon enerjisi izokonversiyonel yöntemlerle hesaplandı. Ayrıca, termoset malzemelerin aktivasyon enerjisini belirlemek için GMN adı verilen yeni sayısal yaklaşım geliştirilmiştir. Prepreg bazlı kompozit laminatların üretimi için sadece vakum torbası (VBO) yöntemi uygulandı. CFRP numunelerinin lif hacim fraksiyonları %55.3 ile %50.16 arasında değişmiştir. F-SWCNT'leri olan/olmayan prepreg bazlı CFRP kompozitlerin mekanik ve termomekanik özellikleri araştırıldı. F-SWCNT'lerle doldurulmuş CFRP kompozitinin optimum mekanik özellikleri, F-SWCNT'lerin ağırlıkça %0.05'inde elde edildi. Bununla birlikte, saf CFRP ile karşılaştırıldığında, daha yüksek F-SWCNT içeriğinin eklenmesi ile mekanik özellikler azalmıştır.
Fonksiyonel Dolgular İçeren Yenilikçi Fiber Takviyeli Prepreglerin ve Onların Kompozitlerinin Geliştirilmesi ve Karakterizasyonu
Thesis (Doctoral)--Izmir Institute of Technology, Mechanical Engineering, Izmir, 2021
Includes bibliographical references (leaves. 151-167)
Text in English; Abstract: Turkish and English
Keywords: Prepregs; Fiber reinforced composites; Carbon nanotubes